2020
DOI: 10.2147/nss.s279088
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Sleep Time Duration Does Not Affect Oral Inflammation and Periodontal Health Status in Night-Shift Workers: A Cross-Sectional Study</p>

Abstract: Background: Night-shift workers experience circadian rhythm disruption, changes in sleep time duration, and effects on their eating habits. All these factors may be related to the release of inflammatory mediators and may affect oral inflammation and periodontal health status. The objective of this study was to analyze the effects of sleep time duration on oral inflammation and periodontal health status in night-shift workers and non-night-shift workers. Methods: This study involved two groups with 27 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Shift work, irregular sleep and diet, and high mental stress could all lead to rhythm disturbances and are strongly associated with periodontitis. Park JS et al reported that workers with circadian rhythm disorders had higher rates of salivary and gingival crevicular fluid TNF-α levels, oral inflammation and periodontal inflammatory status ( Roestamadji et al, 2019 ; Roestamadji et al, 2020 ). Higher TNF-α levels could cause a reduction in tooth attachment and alveolar bone resorption.…”
Section: Circadian Rhythm/clock Genes Regulate Maxillofacial Embryoni...mentioning
confidence: 99%
“…Shift work, irregular sleep and diet, and high mental stress could all lead to rhythm disturbances and are strongly associated with periodontitis. Park JS et al reported that workers with circadian rhythm disorders had higher rates of salivary and gingival crevicular fluid TNF-α levels, oral inflammation and periodontal inflammatory status ( Roestamadji et al, 2019 ; Roestamadji et al, 2020 ). Higher TNF-α levels could cause a reduction in tooth attachment and alveolar bone resorption.…”
Section: Circadian Rhythm/clock Genes Regulate Maxillofacial Embryoni...mentioning
confidence: 99%
“…A recent study based on the KNHANES demonstrated a significant interaction between work schedule and sleep duration (Park et al, 2021). To date, studies on the interrelationships among sleep duration, sleep patterns, and periodontal health have produced inconsistent results (Roestamadji et al, 2020; Park et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, even though our analyses were adjusted for various potential confounding et al, 2021). To date, studies on the interrelationships among sleep duration, sleep patterns, and periodontal health have produced inconsistent results (Roestamadji et al, 2020;Park et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations